Sex-Specific Associations Between Bipolar Disorder Pharmacological Maintenance Therapies and Inpatient Rehospitalizations: A 9-Year Swedish National Registry Study - Ragazan, Dragos C.; Eberhard, Jonas; Berge, Jonas (Frontiers in Psychiatry, 2020)
Background: Long-term pharmacological maintenance therapy is often essential among people with bipolar disorder to reduce the need for inpatient care. Sex-specific responses to maintenance therapies are expected but remain largely unknown. Here, we examined for sex-specific associations between common maintenance therapies for bipolar disorder with inpatient rehospitalizations following patients’ index discharges during 2006-2014. Methods: Population-based data on maintenance therapies and rehospitalizations were extracted from Swedish national registries. We adopted the within-individual design to compare the time on- versus off- maintenance therapy for males and females, respectively. Extended stratified Cox proportional hazards regression models were employed to quantify the rate of rehospitalization as a function of common maintenance drugs and other important time-varying control variables. Results: Our primary analysis included 22,681 bipolar disorder rehospitalizations by 6,400 males and 9,588 (60.0%) females over an observation time of 62,813 person-years. The time spent on- versus off- maintenance lithium, lamotrigine, quetiapine, or olanzapine was statistically significant upon adjustment among either sex for reducing the rate of bipolar rehospitalizations. Adjusted sex-specific statistically significant associations were also observed. Among females, the time on- (versus off-) long-acting injectable risperidone reduced the rate of bipolar rehospitalizations by 73% (56-84%), carbamazepine by 44% (18-62%), aripiprazole by 29% (13-42%), and valproate by 23% (11-33%); whereas among males, ziprasidone by 65% (41-79%). Conclusion: The effectiveness of most maintenance therapies is generally comparable and uniform among both males and females. Despite some statistically significant sex-specific associations, estimates for each drug were fairly consistent between sexes.